Generation of high-intensity single attosecond x-ray pulses with multi-laser beam superposition - (:unkn) unknown (IOP PUBLISHING LTD, 2019)
The generation of high-intensity single attosecond x-ray pulses from high-order harmonic generation (HHG) has been investigated via superposition of multi-laser beams. The results can be separated into three parts: (i) single-color chirp modulation; (ii) ultraviolet (UV)-chirp two-color modulation; and (iii) multi-laser beam modulation. Firstly, for the single chirp modulation, with the introduction of the up-chirp, although the harmonic cutoff can be slightly extended, the efficiency of the HHG is reduced. With the introduction of the down-chirp, both the cutoff and the efficiency of the HHG can be improved compared with the up-chirp. Moreover, as the pulse duration increases, a larger harmonic cutoff can be found. Secondly, by appropriate addition of a UV pump pulse, the efficiency of HHG can be further enhanced due to UV-resonance-enhancement-ionization. Thirdly, with the assistance of the third controlling pulse or the inhomogeneous effect of the laser field, the harmonic cutoff can be further extended and keV-HHG can be produced. Finally, through Fourier transformation of some selected harmonics on the spectral continuum, high-intensity x-ray pulses (including the keV region) with durations of sub-90 as can be obtained.
Keywords: high-order harmonic generation; single attosecond x-ray source generation; ultraviolet (UV)-chirped laser beam; resonance ionization; inhomogeneous field; ORDER HARMONIC-GENERATION; ENHANCEMENT